STRUKTUR HISTOLOGI HATI TIKUS PUTIH (Rattus norvegicus Berkenhout 1769) DENGAN PEMBERIAN RAMUAN TRADISIONAL MASYARAKAT MELAYU LINGGA, KEPULAUAN RIAU - Fitmawati Fitmawati; Titrawani Titrawani; Welly Safitri (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2018)
Lingga Island is the center of the Malay kingdom of Kepulauan Riau Province with local wisdom that is still ingrained in the community. Obat pahit is a decoction of linguistic stew of ethnic lingga community which is believed to be a youthful remedy and maintain stamina. This study aims to find histopathologic changes of liver white mice after the decoction of herb concoction of Obat pahit. The percentage of intercellular damage was nonexistent from the normal control group and positive control but different from the negative control group. Different types of medicinal herbs with different dosage levels. But the damage is still in the normal, accessible category that has no toxic effects from bitter herbs on liver organ.